Evaluation of outcome following paracervical infiltration with or without saline and adrenaline during vaginal hysterectomy - M., Jayaraman Nambiar; Yettinamani, Bhaygarekha; Pai, Muralidhar V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Paracervical infiltration is used in vaginal hysterectomy to facilitate dissection. Use of paracervical infiltration however can be associated with local ischemia and infection. We did a study to find out its benefits during vaginal hysterectomy. Methods: It was a prospective case control study. Patients were divided into two groups. In the first group, no paracervical infiltration was given. In the second group paracervical infiltration was given before hysterectomy. The operating time, blood loss and postoperative infection were noted in each group. Results: The operating time was slightly higher in vaginal hysterectomy group without infiltration (p=0.025) The operating time in laparoscopic assisted vaginal hysterectomy group was not significant (p=0.0296). There was significant difference in Hemoglobin after surgery in both groups (p value 0.614 for vaginal hysterectomy and 0.173 for laparoscopic assisted vaginal hysterectomy). There was no case of infection in both groups. Conclusions: From our study, we concluded that paracervical infiltration offers no distinctive advantage during vaginal hysterectomy or laparoscopic assisted vaginal hysterectomy.